Casein kinase 2 mediated phosphorylation of Spt6 modulates histone dynamics and regulates spurious transcription. Issue 15 (14th June 2018) - Gouot, Emmanuelle; Bhat, Wajid; Rufiange, Anne; Fournier, Eric; Paquet, Eric; Nourani, Amine
Abstract: CK2 is an essential protein kinase implicated in various cellular processes. In this study, we address a potential role of this kinase in chromatin modulations associated with transcription. We found that CK2 depletion from yeast cells leads to replication-independent increase of histone H3K56 acetylation and global activation of H3 turnover in coding regions. This suggests a positive role of CK2 in maintenance/recycling of the histone H3/H4 tetramers during transcription. Interestingly, strand-specific RNA-seq analyses show that CK2 inhibits global cryptic promoters driving both sense and antisense transcription. This further indicates a role of CK2 in the modulation of chromatin during transcription. Next, we showed that CK2 interacts with the major histone chaperone Spt6, and phosphorylates it in vivo and in vitro . CK2 phosphorylation of Spt6 is required for its cellular levels, for the suppression of histone H3 turnover and for the inhibition of spurious transcription. Finally, we showed that CK2 and Spt6 phosphorylation sites are important to various transcriptional responses suggesting that cryptic intragenic and antisense transcript production are associated with a defective adaptation to environmental cues. Altogether, our data indicate that CK2 mediated phosphorylation of Spt6 regulates chromatin dynamics associated with transcription, and prevents aberrant transcription.